Observations of aerosols from space : An overview - VINOJ, V.; SATHEESH, S. K. (MAUSAM, 2003)
Aerosols are of natural and anthropogenic (man-made) origin. Aerosols directly affect the climate by scattering and absorption of solar and terrestrial radiation and indirectly by enhancing the reflectivity of clouds by acting as cloud condensation nuclei. Estimation of effects of aerosols on climate is complicated by the fact that their chemical composition, abundance and size characteristics are highly variable both spatially and temporally. Measurement of aerosols can be in situ (direct) or remote. For mapping aerosol properties on a regional or global scale, satellite based remote sensing is the only option. For the remote sensing of surface such as ocean or land, algorithms should include atmospheric corrections to correct for the atmospheric effect to satellite measured signals. However, remote sensing of aerosol properties such as its chemical composition is still extremely difficult. In this paper, we review the investigations of aerosols using satellite data with emphasis to Indian region. Various sensors and algorithms used for the remote sensing of aerosols and future scope are also discussed.